PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA PADA USAHA KONVEKSI RUMAHAN “CAHAYA TAILOR”. - Manah Tarman; Ika Lis Mariatun (Universitas PGRI Adi Buana Surabaya, 2025)
Micro, small and medium enterprises (MSMEs) play an important role in local economic growth, including home-based garment businesses such as Cahaya Tailor, which was established in May 2020 on Jl. Anggrek Mlajah, Bangkalan District. This business serves the manufacture of clothing such as school uniforms, office uniforms, kebaya, jackets, alma maters, and others. However, business owners do not yet have a structured financial recording system. This community service aims to assist business actors in preparing simple financial reports so that they can manage finances effectively. The activity was carried out on April 16, 2025 and the results showed an increase in understanding and ability of business actors in recording business income and expenses in a simple and systematic manner.